Molecular pathways in reproductive cancers: a focus on prostate and ovarian cancer - Ayodeji Folorunsho Ajayi; Mega Obukohwo Oyovwi; Oyedayo Phillips Akano; Grace Bosede Akanbi; Florence Bukola Adisa (Cancer Cell International)
Abstract Reproductive cancers, including prostate and ovarian cancer, are highly prevalent worldwide and pose significant health challenges. The molecular underpinnings of these cancers are complex and involve dysregulation of various cellular pathways. Understanding these pathways is crucial for developing effective therapeutic strategies. This review aims to provide an overview of the molecular pathways implicated in prostate and ovarian cancers, highlighting key genetic alterations, signaling cascades, and epigenetic modifications. A comprehensive literature search was conducted using databases such as PubMed, Web of Science, and Google Scholar. Articles focusing on molecular pathways in prostate and ovarian cancer were reviewed and analyzed. In prostate cancer, recurrent mutations in genes like AR, TP53, and PTEN drive tumor growth and progression. Androgen signaling plays a significant role, with alterations in the AR pathway contributing to resistance to antiandrogen therapies. In ovarian cancer, high-grade serous carcinomas are characterized by mutations in TP53, BRCA1/2, and homologous recombination repair genes. PI3K and MAPK pathways are frequently activated, promoting cell proliferation and survival. Epigenetic alterations, including DNA methylation and histone modifications, are also prevalent in both cancer types. The molecular pathways involved in prostate and ovarian cancer are diverse and complex. Targeting these pathways with precision medicine approaches holds promise for improving patient outcomes. Further research is needed to elucidate the mechanisms of resistance and identify novel therapeutic vulnerabilities.